If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 5 + -2 = 3 + x Reorder the terms: 5 + -2 + x = 3 + x Combine like terms: 5 + -2 = 3 3 + x = 3 + x Add '-3' to each side of the equation. 3 + -3 + x = 3 + -3 + x Combine like terms: 3 + -3 = 0 0 + x = 3 + -3 + x x = 3 + -3 + x Combine like terms: 3 + -3 = 0 x = 0 + x x = x Add '-1x' to each side of the equation. x + -1x = x + -1x Combine like terms: x + -1x = 0 0 = x + -1x Combine like terms: x + -1x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 10-2x=4x+3 | | 3/5x-3/2=1/10 | | 4x^6-8x^3/2x^3 | | 5-3x=1+4 | | 6t^2-420t+3549=0 | | 0.75x-12=0.50x-6 | | 6m+5n-4m+8n= | | 12/8=q/11 | | (3+2i)x+(2-2i)y=17-2i | | (19/x)=(9/5) | | 6-r/7=21 | | 2x+(9+x)=-6 | | x^4+4x^3-35x^2+34x+24=0 | | 6x-8x^3=0 | | 1/x=1.211 | | 700+15m=750 | | 2a+10=7-9a | | 112-x=8 | | f(x)=(x-2)(x-5)(x+5i)(x-5i) | | x-4=2-4 | | (x-2)(x-5)(x+5i)(x-5i)=0 | | x+4x-7=0 | | w/4-3=w/3 | | 5(10-2x)-5x= | | (X+2)(X+5)=(X-3)(X-3) | | 1.2-.2=1 | | 7(k+10)=56 | | 2b^2+2b=364 | | V(x)=-5x^2+50x | | 6cosx=1.7 | | 2b^2+2b=91 | | 13N+2N=120 |